Editor Choice-The Oretical Approaches For The Analysis Of Innovation Capacity As A Factor That Affects The Competitiveness Of Software Industry Of Jalisco - Vargas Hernández, José Guadalupe; Calle Medrano, MarÃa José (Journal of Business Management and Economics, 2017)
The aim of this work is to review the theoreticalÂ approached to analyze the innovation capacity of enterprises in the software industry of Jalisco, based on a survey of the companies in the Software Center of the State, as well as evaluating the influence that has the capacity for innovation on competitiveness, seeking empirical evidence to answer the question. The main hypothesis for this research is the ability to innovate is a factor that positively affects the performance of companies in the software industry, which is reflected in the competitiveness of sector. The methods used in this research are three:innovativeness index(ICI), Linear Regression Model with OLS and Soft Computingusing evolutionary algorithms: FUZZYCESAR, the latter something very newwhich puts us inthe forefront of knowledgein methodsit isstill.